2021
DOI: 10.1111/nicc.12708
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of critical care nurses' stress, anxiety, and depression in response to COVID‐19 pandemic

Abstract: Background The coronavirus disease 2019 (COVID‐19) pandemic directly affects the psychological well‐being of critical care nurses. Several studies had investigated the psychological impact of the pandemic on nurses caring for patients with COVID‐19, but few were conducted to identify the predictors of this impact. Aims The objective of this study is to identify the predictors of critical care nurses' stress, anxiety, and depression in response to the COVID‐19 pandemic. Design A cross‐sectional survey was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Having a personal history of any pathology that increased susceptibility to COVID-19 infection was related to higher levels of anxiety and depression, which may be due to a greater concern about infection and its consequences as it implies a higher risk in this group of people. In other areas, similar results have been observed for the presence of depressive symptoms [ 92 ] but not for the anxious type [ 93 , 94 ]. Among HPs from other areas, having a personal history of any mental health disorder, especially those related to substance abuse or depression, was strongly associated with the presentation of a current mental disorder.…”
Section: Discussionsupporting
confidence: 79%
“…Having a personal history of any pathology that increased susceptibility to COVID-19 infection was related to higher levels of anxiety and depression, which may be due to a greater concern about infection and its consequences as it implies a higher risk in this group of people. In other areas, similar results have been observed for the presence of depressive symptoms [ 92 ] but not for the anxious type [ 93 , 94 ]. Among HPs from other areas, having a personal history of any mental health disorder, especially those related to substance abuse or depression, was strongly associated with the presentation of a current mental disorder.…”
Section: Discussionsupporting
confidence: 79%
“…Besides, a previous research study 29 found that 43% of nurses in the CCU had moderate to severe levels of stress, 82% had moderate to very severe levels of anxiety and 40% had moderate to severe levels of depression. In a study conducted with a sample of critical care nurses during the COVID‐19 pandemic, 48.5% of nurses had severe or extremely severe stress levels, 62% had severe levels of anxiety, and 34.5% had moderate levels of depression 30 …”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted with a sample of critical care nurses during the COVID‐19 pandemic, 48.5% of nurses had severe or extremely severe stress levels, 62% had severe levels of anxiety, and 34.5% had moderate levels of depression. 30 …”
Section: Discussionmentioning
confidence: 99%
“…This trend could undoubtedly affect the nursing practice environment for ICU nurses, and administrators should pay more attention to these changes and provide maximum support. A few studies have also shown that some ICU nurses experience physical disorders (e.g., sleep disturbances and headaches) and psychological symptoms (e.g., anxiety, depression and, in severe cases, suicidal contemplations) while caring for COVID‐19 patients (Baraka et al, 2021; Endacott et al, 2022; Gualano et al, 2021). A national survey in the USA of critical care nurses' experiences during the COVID‐19 pandemic showed that nurses perceived inadequate leadership support and inequities within the health care team (Guttormson et al, 2021).…”
Section: Discussionmentioning
confidence: 99%